Policy and innovation network: a study of inter-agency collaboration in post-disaster rehabilitation and reconstruction in the Central Sulawesi, Indonesia - Mohammad Rusli Syuaib (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
The idea of the policy and innovation network in the context of post-disaster governance refers to a set of rules, legislation, regulations, and guidelines that offer guidance for the efforts of post-disaster recovery and reconstruction. The objective of this study is to investigate the impact of policies and innovation networks on post-disaster rehabilitation in a specific geographical region. The research methodology employed in this study is qualitative in nature. The present study employed a diverse range of research data obtained from interviews and disaster management report documents. These data were subsequently subjected to analysis applying the Nvivo12 plus software. The findings of the research suggest that the post-disaster rehabilitation network involves a range of components, specifically the public policy network which comprises the central government, regional governments, associated institutions, and civil society organisation. The local government of Palu City adopted policy changes that prioritised the implementation of a land acquisition and resettlement action plan in the context of post-disaster rehabilitation and construction efforts.